(untitled) (Collection of scientific works «Modern structures of metal and wood», 2023)
In the article are presented the main results of experimental studies of deformability of the reinforcement of common damaged and brought, in the course of the previous tests, to the critical state by the 1st group r.c. beams reinforced with carbon fibre (CFRP) sheet in the lower tensioned zone and on the support area. Namely, according to the results of the experiment, using the COMPEX program, adequate mathematical models of the deformations of steel reinforcement of CFRP-strengthened reinforced concrete specimens-beams under the action of low-cycle sign-constant loading were derived, that reflect the influence of these factors both individually and in interaction with each other. Analyzing these models, the features of the development of tensile reinforcement in the specified conditions, were established. In particular, the factors that have the greatest influence on deformations are the relative shear span and the level of low-cycle loading. As compared with the series of tests of ordinary r.c. samples, presence of the external CFRP strengthening reduced deformation of the tensioned steel reinforcement by 1.65 times on the average. There occurs a re-distribution of the tension forces between them.